(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Vajeekarana, also known as Vrishya Chikitsa, is one of the eight key specialties of Ashtanga Ayurveda. Vajikarana is concerned with aphrodisiacs, virility, and increasing the health of offspring. Ashtanga Hridaya is one Among Bruhatrayee (Greater Trio). Acharya Vagbhata writen the two most important classics like Ashtanga Sangraha and Ashtanga Hridaya. Due to its superior organisation and concision over Ashtanga Sangraha, Ashtanga Hridaya is a far more approachable classic. Vajeekarana vidhi (Aphrodisiac therapy) is explained in the last chapter of Uttarasthana of Ashtanga hrudaya. According to WHO, Millions of people battle with infertility. One in six people who are of reproductive age worldwide are predicted to become infertile at some point in their lives. Several parts of the world, particularly low- and middle-income nations, still lack access to most modern therapies and their cost is prohibitive. Many Vajikarana yogas are (Aphrodisiac Formulations) mentioned in Ayurvedic classics which are cheaper,easier to prepare, safer and effective. This review Article focuses on unique contribution on Vajeekarana yogas mentioned by Acharya Vagbhata in Ashtanga Hridaya.